Diagnostic accuracy of Magnetic Resonance Imaging (MRI) Knee in detecting Anterior Cruciate Ligament (ACL) tear taking arthroscopy as gold standard. (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the diagnostic accuracy of MRI in detecting ACL tears in patients presenting with knee injury taking arthroscopy as gold standard.Methods: This Cross sectional study was conducted in department of Orthopedic Surgery Khyber Teaching Hospital Peshawar from 2nd February 2019 to 28th August 2020. All patients with clinical ACL tear fulfilling the inclusion criteria had MRI of the knee joint followed by arthroscopy. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and diagnostic accuracy of MRI was calculated with reference to arthroscopy as gold standard.Results: The total number of patients in our study was 106 with mean age 32±9 years. Male patients were 77 (72.64%) and female 29 (27.35%) were female. Left knee was involved in 67 (63.20%) patients and right in 39 (36.79%).ACL tear was noted in 43 (40.56%) patients on MRI while 86 (81.13%) patients had ACL tear diagnosed on arthroscopy. Sensitivity of MRI was 66.67%, specificity 75.90%, PPV 81.13%, NPV 59.43% and diagnostic accuracy 70.28%.Conclusion: MRI is a useful diagnostic modality but we found low diagnostic accuracy of MRI for ACL tear considering arthroscopy as gold standard. Diagnostic arthroscopy is therefore recommended for confirming ACL tear in doubtful cases.